Capitalism in pre-colonial Africa: a review - Morten Jerven (African Economic History Network (AEHN), 2016)
To what extent did capitalism come into being in Africa before 1850? If by capitalism we mean the production of goods for exchange by capitalists who combine their own capital and land with labor bought from free workers without land, then the accumulative historical evidence tells us that only to a limited extent had capitalism emerged before 1850, and it was most certainly not the dominant system of production in Africa (Iliffe 1983). This does not mean that there was no production for the market. Nor does it imply that there was no wage labor, or that exchanges of capital did not take place. Finally it does not mean that there was no economic growth in Sub-Saharan Africa before 1850. As will be analyzed here, markets did exist, there were some wage labor and there were means of exchange that facilitated some economic growth, though growth mostly occurred on the extensive margin.
Keywords: N17; N27; N37; N57; N67; 330; Pre-colonial; Africa; Capitalism; Labour